Analyzing Communication Strategies of the Saudi Ministry of Health During COVID-19 (American Journal of Arts and Human Science, 2023)
Effective communication is imperative during crises such as the COVID-19 Pandemic. The study investigates the communication strategies employed by the Saudi Ministry of Health through its official Twitter account during the pandemic. A content analysis of 1129 Tweets from the Saudi Ministry of Health’s official Twitter account was conducted from January 21, 2020, to July 21, 2020. Twitonomy software was used to collect the tweets. A coding sheet was developed and validated for measuring communication strategies, content types, language, target audience and user interaction. The results demonstrate that the Saudi Ministry of Health utilized an “information strategy” (74%) to communicate with the public. Most tweets included infographics (75.9%), followed by videos (16,95%). Text-only tweets (2%) and links to external websites (0.35%) were less absent. Arabic was the predominant language (86%), followed by English (12%), and a mix of ten other languages (2%). This study emphasizes the value of understanding audience dynamics for upcoming crisis communication strategies as well as the significance of effective communication in public health crises. The results can help public health authorities approach similar circumstances more effectively and effectively.